Emerging therapies in sickle cell disease. (6th March 2020) - Nardo‐Marino, Amina; Brousse, Valentine; Rees, David
Summary: Despite sickle cell disease (SCD) being the most common and severe inherited condition worldwide, therapeutic options are limited. To date, hydroxyurea remains the main treatment option in SCD. However, in the last decade the numbers of interventional clinical trials focussing on therapies for SCD have increased significantly. Many new drugs with various pharmacological targets have emerged and, although the majority have failed to show benefit in clinical trials, some have produced encouraging results. It seems probable that more drugs will soon become available for the treatment of SCD. Furthermore, promising clinical trials with improved outcomes have recently changed the perspective of curative therapies in SCD. Nevertheless, the application of novel therapeutic agents and potential curative treatments will most likely be limited to high‐income countries and, thus, will remain unavailable for the majority of people with SCD in the foreseeable future.